The Discourse of Propaganda: Case Studies from the Persian Gulf War and the War on Terror by John Oddo (A Book Review) - Gumuła, Piotr (Review of International American Studies, 2021)
Piotr Gumuła's review of John Oddo's The Discourse of Propaganda: Case Studies from the Persian Gulf War and the War on Terror. Pennsylvania State UP, 2018.